Pemasaran Digital dan Pre-Order melalui Instagram, Marketplace, dan WhatsApp Business UMKM Dapur Qayla Kelurahan Margomulyo - Annisa Anindya Eka Putri; Afni Dwi Febrianti Habibah; Tiara Anggreini Amanda; Putri Julianti; Endah Puspita Sari; Mira Suradi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This project enhanced digital visibility, established a structured pre-order workflow, and built practical content-creation capacity for micro and small enterprises (UMKM) through a blended approach of on-site assistance and targeted digital interventions. Methods combined needs assessment, identity and packaging redesign, provision of physical display assets, activation and optimization of Instagram Business and marketplace listings, creation of a consolidated Linktree to WhatsApp and Google Maps, and hands-on training in Canva and AI-assisted photo editing, culminating in a one-day seminar and workshop. Monitoring for the August–October period recorded 4,147 Instagram impressions and active participation by 17 local UMKM operators in the seminar. Findings indicate measurable gains in online exposure, improved content production efficiency, and strengthened alignment between online promotion and offline credibility. Key outcomes include higher feed consistency, faster content turnaround, and increased user engagement through video route guides and customer testimonials. Constraints included intermittent internet access and the need for ongoing catalog maintenance. The intervention is feasible for replication with adaptations for connectivity and management capacity. Recommended next steps are systematic catalog management training, a concise standard operating procedure for AI and Canva content workflows, and targeted paid-promotion trials to expand reach among non-followers.